SEKILAS MENGENAI HUMAN COMMUNICATION (KOMUNIKASI INSANI ) VERBAL MAUPUN NONVERBAL Brief On Human Communication (Communication lnsani) Verbal Or Nonverbal - Kertopati, Ton (Universitas Prof. Dr. Moestopo (Beragama), 2010)
Communication transaction: basic elements and factors, so far as the communicator concerned all the Communications transactions are shaped by some important influence such as.The communicative purpose and knowledge of the subject.The purpose in communicating is to attain some goal and the effectiveness with which it is transmitted.Besides of knowledge of subject matter fundamental skills is important regardless of the situations in which a communication transaction occurs verbal or nonverbal communication symbol.The ability to use our voices and bodies to express ideas orally and visually facilitates the understanding and acceptance basic to successful functioning of communication process.